Adverse childhood experiences and their relationship to gender and depression among young adults in Iraq: a cross-sectional study - Al Shawi, Ameel F. (BMC Public Health, 2019)
BACKGROUND: Adverse childhood experiences (ACEs) are considered as universal public health problem that associate with mental disorders and risky behaviors during adulthood. The aims of the paper are to estimate the prevalence of Adverse childhood experiences (ACEs) among young adults in Iraq as well as to estimate the association between ACEs and depression. METHODS: A convenience sample of young adults of 18–20 years was chosen from centre and west of Iraq, mainly from universities. The adverse childhood experiences were measured by Adverse Childhood Experiences Questionnaire. A depression scale was derived from the Depression, Anxiety and Stress Scales (DASS). Statistical tests: chi square was used to measure the association between adverse childhood experiences and other variables like gender and depression. Odds ratios were computed to estimate the risk for depression. A P value of less than 0.05 was considered statistically significant. RESULTS: The total number of participants was 401, 38.9% of the subjects were men, while 61.1% were women. The mean age of the participants was 18.88 ± 0.745. The results revealed that the most common forms of ACEs among the subjects were physical neglect (19.8%) and emotional neglect (19.2%) followed by physical abuse (17.21%) while sexual abuse was 7.52%. There was statistically significant association between most forms of adverse childhood experiences especially emotional abuse, emotional neglect, physical abuse and physical neglect with depression. CONCLUSION: ACEs are not uncommon among young adults in Iraq and are associated with depression in adulthood. National programmes to support mental health rehabilitation might be necessary to reduce the effect of ACEs among Iraqi people, especially for adolescents and young adults.